1992
DOI: 10.1111/j.1365-2958.1992.tb00896.x
|View full text |Cite
|
Sign up to set email alerts
|

Stabilization of bacteriophage Mu repressor‐operator complexes by the Escherichia coli integration host factor protein

Abstract: All of the previously described effects of integration host factor (IHF) on bacteriophage Mu development have supported the view that IHF favours transposition-replication over the alternative state of lysogenic phage growth. In this report we show that, consistent with a model in which Mu repressor binding to its operators requires a particular topology of the operator DNA, IHF stimulates repressor binding to the O1 and O2 operators and enhances Mu repression. IHF would thus be one of the keys, besides superc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
21
0

Year Published

1993
1993
2001
2001

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 37 publications
1
21
0
Order By: Relevance
“…11,+6) vir3061 (-23,+13) proposed that binding of IHF to its cognate site located between O1 and 02 provides the right conformation for optimal repressor binding (Vogel et aI., 1991). This was confirmed by both in vivo and in vitro experiments which showed that IHF increases repression by repressor in vivo and facilitates repressor binding to the operators in vitro (Gama, Toussaint & Higgins, 1992;Alazard, B6termier & Chandler, 1992). The host H-NS protein, another nucleoid associated histone-like protein, has similar effects on repression and repressot binding as IHE Its exact mechanism of action is unknown and although it has been proposed that H-NS acts through protein-protein interactions with repressor (Falconi et al, 1991), the possibility remains open that H-NS binds DNA in the operator region, as it does for instance in the rrn promoters (Tippner et al, 1994).…”
Section: Lysogenysupporting
confidence: 75%
“…11,+6) vir3061 (-23,+13) proposed that binding of IHF to its cognate site located between O1 and 02 provides the right conformation for optimal repressor binding (Vogel et aI., 1991). This was confirmed by both in vivo and in vitro experiments which showed that IHF increases repression by repressor in vivo and facilitates repressor binding to the operators in vitro (Gama, Toussaint & Higgins, 1992;Alazard, B6termier & Chandler, 1992). The host H-NS protein, another nucleoid associated histone-like protein, has similar effects on repression and repressot binding as IHE Its exact mechanism of action is unknown and although it has been proposed that H-NS acts through protein-protein interactions with repressor (Falconi et al, 1991), the possibility remains open that H-NS binds DNA in the operator region, as it does for instance in the rrn promoters (Tippner et al, 1994).…”
Section: Lysogenysupporting
confidence: 75%
“…Binding of IHF to the early operator region of Mu (39,69) can influence transcriptional control in different ways. By stabilizing the interaction of the repressor with sites 01 and 02, it may favor lysogeny (19,20), whereas in the absence of c (i.e., during lytic growth), it stimulates early transcription (23,39). In addition, IHF binding to the IAS directly stimulates in vitro transposition of a substrate with suboptimal supercoiling levels (62,64).…”
mentioning
confidence: 99%
“…IHF plays an architectural role in the formation of various nucleoprotein complexes involved in different phenomena such as transcription activation, transcription repression, site-specific recombination, transposition, initiation of DNA replication, and plasmid partition. Binding of IHF could create a loop which stabilizes interaction of Roi with its binding site(s): this is reminiscent of the stabilization of the Mu repressor interaction with its operator (1,12). Interestingly, we noted the presence of an IHF binding site in the gene that encodes the related P1 Ant1 protein (from nt 855 to 867 in the sequence reported by Heisig et al [17]).…”
Section: Discussionmentioning
confidence: 75%
“…We speculated that IHF could bind the ihf site within the roi gene and possibly stabilize the interaction of the DNA-binding Roi protein with its target DNA, as happens in Mu repressor-operator interaction (1,12). The target of the Roi protein might then be located near the ihf site.…”
mentioning
confidence: 99%